Effect of the microfiltration process on antioxidant activity and lipid peroxidation protection capacity of blackberry juice - Azofeifa Cordero, Gabriela (2011)
Phytochemicals are highly concentrated in berries, especially polyphenols as anthocyanins and ellagitannins. These compounds have been associated with antioxidant capacity, lipid peroxidation protection, anti-inflammatory activity, anti carcinogenic activity, obesity prevention and others. Blackberries are commonly grown and consumed as juice in Latin-American countries. However, blackberry juice is easily fermented and different industrial techniques are being applied to enable the juice to be stored for longer periods. One important issue required for these techniques is to preserve the health-promoting capacities of blackberries. This study compared the antioxidant activity and the lipid peroxidation protector effect between a fresh blackberry juice (FJ) and a microfiltrated blackberry juice (MJ). Chemical analysis of both juices show less polyphenols concentration in the MJ. Despite this difference, values for biological activities, such as protection of lipid peroxidation, was not significantly different between FJ and MJ. These results suggest that the compounds responsible for the antioxidant activity are maintained even after microfiltration and the free radical scavenging capacity of these compounds could protect the initiation of lipid peroxidation. Microfiltration could be used as an industrial technique to produce blackberry juice that maintains biological activities of polyphenols.